Group portrait of the California State Grange women's team in Campbell, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the California State Grange women's team posing in front of unidentified building in Campbell, California. The main entrance of the building has two building name plaques, one each on the left and right side of the entry door. The left plaque reads: "Campbell Hamilton;" the right plaque reads: "Cambrian San Tomas." With few exceptions, every woman is dressed in a formal white gown, crowned with a shimmering headband, and holding a flower bouquet.